Safety of endovascular treatment in acute stroke patients taking oral anticoagulants. Issue 4 (June 2017) - Uphaus, Timo; Singer, Oliver C; Berkefeld, Joachim; Nolte, Christian H; Bohner, Georg; Niederkorn, Kurt; Deutschmann, Hannes; Haring, Hans-Peter; Trenkler, Johannes; Neumann-Haefelin, Tobias; Hofmann, Erich; Stoll, Anett; et al.
Background: The endovascular treatment of acute cerebral ischemia has been proven beneficial without major safety concerns. To date, the role of endovascular treatment in patients treated with oral anticoagulants, which may be associated with periprocedural intracranial bleeding, remains uncertain. Aims: The objective of the current analysis is to evaluate the safety of endovascular treatment in patients treated with oral anticoagulants. Methods: The ENDOSTROKE-Registry is a commercially independent, prospective observational study in 12 stroke centers in Germany and Austria collecting pre-specified variables about endovascular stroke therapy. Results: Data from 815 patients (median age 70 (interquartile range (IQR) 20), 57% male) undergoing endovascular treatment with known anticoagulation status were analyzed. A total of 85 (median age 76 (IQR 8), 52% male) patients (10.4%) took vitamin-K-antagonists prior to endovascular treatment. Anticoagulation status as measured with international normalized ratio was above 2.0 in 31 patients. Intracranial hemorrhage occurred in 11.8% of patients taking vitamin-K-antagonists compared to no-vitamin-K-antagonists (12.2%, p = 0.909). After adjustment for confounding factors which were unbalanced at univariate level such as NIHSS and age, anticoagulation status was not found to significantly influence clinical outcome (modified Rankin Scale 3–6) and occurrence of intracranial hemorrhage in a multivariate logistic regression analysis. Conclusion: Prior use of vitamin-K-antagonists was not associated with a higher rate of periprocedural intracranial hemorrhage after endovascular treatment or worse outcome. Endovascular treatment should be considered as an important treatment option in patients taking vitamin-K-antagonists.